2023
DOI: 10.2217/fon-2022-1016
|View full text |Cite
|
Sign up to set email alerts
|

High tumor burden in patients with non-small-cell lung cancer: a Delphi survey among Spanish oncologists

Abstract: Aim: To define high tumor burden (HTB) in non-small-cell lung cancer. Methods: A total of five oncologists initiated the project, selecting 66 participants, and elaborated a questionnaire with 26 statements using the Delphi method with a 9-point Likert scale of agreement. Results: Factors with moderate strength of consensus were identified, including a sum of the longest diameter of lesions ≥10 cm, elevated LDH, hepatic involvement, lymphangitis carcinomatosis, brain involvement unapproachable with local techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Tumor burden simply indicates the total amount of tumor in the body. Accumulating studies have demonstrated that tumor burden is an independent prognostic factor with a negative impact on survival in several types of malignancies, including melanoma [14], lung cancer [15][16][17][18], head and neck cancer [19,20], thyroid cancer [21] and lymphoma [22]. Kim et al conducted a systematic review and identified the negative impact of tumor burden on baseline immunity and treatment-induced immune responses [7].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor burden simply indicates the total amount of tumor in the body. Accumulating studies have demonstrated that tumor burden is an independent prognostic factor with a negative impact on survival in several types of malignancies, including melanoma [14], lung cancer [15][16][17][18], head and neck cancer [19,20], thyroid cancer [21] and lymphoma [22]. Kim et al conducted a systematic review and identified the negative impact of tumor burden on baseline immunity and treatment-induced immune responses [7].…”
Section: Discussionmentioning
confidence: 99%